"I think people have been in survival mode": a qualitative study of community connectivity in a neighbourhood of North East England before and during COVID-19. Issue 7 (12th July 2022) - Cheetham, Mandy; Gorman, Sarah; Pollard, Fiona; Ward, Stephen; Wiseman, Alice
Abstract : Objectives: The aim of the study was to examine whether and how community-centred approaches facilitate community connectivity by exploring changes that matter to communities. Design: Qualitative study comprising ethnographic methods, participant observation and interviews.Setting Economically deprived neighbourhood of North East England. Participants: Interviews with community members (n=14) and staff and stakeholders (n=14) involved in a National Lottery Community-funded initiative and 567 hours of participatory observation were undertaken between September 2019 and July 2020. Data were thematically analysed using a community-centred public health framework. Results: Communities experiencing disadvantage approached the pandemic adversely affected by stigma, austerity and reductions in public sector funding. Community members' priorities centred on the environment, housing, activities for children and young people, crime, community safety and area reputation. Multiagency efforts to promote connectivity, led by voluntary and community sector organisations, were prerequisites in community-centred approaches to public health. Stakeholders reported that these approaches can help alleviate some of the health, social and financial burdens facing communities that are marginalised. Findings suggest community-centred responses were facilitated by trusting relationships, visionary leadership and lived experience of adversity among staff. Issues which appeared to hamper progress included interorganisational power dynamics and attempts to impose solutions. The strength of stakeholders' connections to the area and to people living there contributed to laying the foundations for local responses to the COVID-19 pandemic. Relational, values-informed work with communities provided a platform to mobilise recovery assets. Conclusions: Whole-system approaches, codesigned with communities most affected, can help address the long-term consequences of COVID-19 and its negative effects on health and social inequalities. Further comparative implementation research is needed to examine the partnerships, values and principles that drive success and inclusion.